(untitled) (KULT_online, 2013)
Each essay in Travelling Concepts for the Study of Culture introduces a concept that has substantially travelled in the humanities and beyond, such as gender, performance or narrative. The volume shows how these concepts travel through time and space as well as through different disciplines and how they are transformed on the way. While Cultural Studies and Kulturwissenschaften are the focus of the book, it is in continuous dialogue with other disciplines of the humanities, such as history and literature, that remain crucial points of reference in the journey of concepts.